Personhood and dignity at the beginning of life: the conceived by in vitro fertilization in Chile - Ramos Vergara, Paulina; Arenas Massa, Ángela; Santos Alcántara, Manuel (Acta Bioethica, 2014)
The present study analyzes some of the problems encountered in Chile in the beginning of life of those conceived by in vitro fertilization. From these arises the need to norm the application of these techniques with the goal to protect life in compliance with constitutional mandate. This is a descriptive historical study grounded on the review of Chilean project laws regulating the issue —direct and indirectly— between 1996 and 2013. It is concluded that is urgent to regulate a juridical statue of the unborn conceived to guaranty the effective integrity of his/her life.